Improving Student Learning Outcomes Through CTL Approach To The Material For Reducing Fractions - Yulianti Yulianti; Akina Akina; Herlina Herlina (Universitas Tadulako, 2020)
The purpose of this study was to obtain a description of improving students learning outcomes through the Contextual Teaching and Learning (CTL) Approach on Fractional Reduction Material in Class V SDN 16 Sindue in the academic year 2018 / 2019. This research is a classroom action research in the form of a cycle in which the cycle is divided of the four stages, namely (1) planning, (2) action, (3) observation, and (4) reflection. For the location of this study, SDN 16 Sindue focused on class V with a total of 16 students. Data collection techniques in this study were (1) giving tests, (2) observation / observation, (3) interviews, and (4) documentation. Data analysis techniques used in this study are quantitative and qualitative. Learning conducted in this study was divided into 2 cycles with the following results: an increase in the results of the average value of the first cycle that is 76, 56in the good category rose 9.37 to 85.93in the second cycle into the very good category. Furthermore, classically it can be seen to increase from the activities of the first cycle by 75% in the good category up 12.5% to 87.5% in the second cycle in the very good category.